Analysis and Design of a Discrete-Time Delta-Sigma Modulator Using a Cascoded Floating-Inverter-Based Dynamic Amplifier - Kumar, R. S. Ashwin; Krishnapura, Nagendra; Banerjee, Paramita (IEEE journal of solid-state circuits, 2022)
This article presents a delta-sigma modulator (DSM) using a cascoded floating-inverter-based dynamic amplifier. The proposed cascoded dynamic amplifier achieves more than 50-dB dc gain while maintaining an HD3 of better than -110 dBc for signal swings less than 300~\mathrm {mV_{ppd}} . Compared to the previously reported two-stage floating inverter amplifier (FIA), the cascoded FIA has a lower and a process invariant input-referred noise, making it an ideal choice for high-resolution ADCs. We also show that, when such a single-stage dynamic amplifier, which has a time-varying transconductance, is used in closed-loop switched-capacitor circuits, the settling bandwidth depends on the average transconductance G_{m,\rm avg} during the settling interval. A detailed analysis reveals that, when the floating inverter structure operates in weak inversion for most of the time (which is the power-efficient way to bias the amplifier), this average transconductance depends strongly on the reservoir capacitance value and only weakly on the transistor dimensions. Besides, it is less sensitive to temperature variations, unlike the transconductance of a conventional OTA biased in weak inversion. We also quantitatively derive and show that the cascoded FIA is more power-efficient than a conventional static-current biased operational transconductance amplifier. Using the cascoded FIA, a discrete-time DSM has been designed and fabricated in a 180-nm CMOS process. The modulator runs at 3.072 MHz while consuming 189 μ \text{A} from a 1.8-V supply. In a bandwidth of 24 kHz, the measured SNR/SNDR/SFDR is 96.4/96.2/114 dB, respectively.